2016
DOI: 10.3390/ijerph13111156
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Rurality and Disadvantage on the Diagnostic Interval for Breast Cancer in a Large Population-Based Study of 3202 Women in Queensland, Australia

Abstract: Delays in diagnosing breast cancer (BC) can lead to poorer outcomes. We investigated factors related to the diagnostic interval in a population-based cohort of 3202 women diagnosed with BC in Queensland, Australia. Interviews ascertained method of detection and dates of medical/procedural appointments, and clinical information was obtained from medical records. Time intervals were calculated from self-recognition of symptoms (symptom-detected) or mammogram (screen-detected) to diagnosis (diagnostic interval (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 54 publications
1
19
1
Order By: Relevance
“…Results from previous research in breast cancer are similarly mixed. For example, another Australian study also found no rural-urban variation in the patient interval, but unlike our study, symptomatic and screen-detected rural women were more likely to have a diagnostic interval >30 days than urban women (44). A U.S. study found no geographic differences in time from mammography to treatment for women in the National Breast and Cervical Cancer Early Detection Program, however, rural women had a quicker diagnostic interval than metropolitan women (45).…”
Section: Discussioncontrasting
confidence: 84%
“…Results from previous research in breast cancer are similarly mixed. For example, another Australian study also found no rural-urban variation in the patient interval, but unlike our study, symptomatic and screen-detected rural women were more likely to have a diagnostic interval >30 days than urban women (44). A U.S. study found no geographic differences in time from mammography to treatment for women in the National Breast and Cervical Cancer Early Detection Program, however, rural women had a quicker diagnostic interval than metropolitan women (45).…”
Section: Discussioncontrasting
confidence: 84%
“…It is possible that women in the unscreened cohort may have had a mammogram outside of the three included sources used in our study. That said, these three sources represent the largest providers of mammogram services in Queensland, and our screening rate of around 78% is in line with published screening rates from BSQ (54%), plus estimates of an additional 20% performed in private facilities . It should also be acknowledged that the findings in our study may be subject to some bias as our “unscreened” group included women with no history of screening for the period 2000–2005, that is, we made no provision for a history of screening prior to 2000.…”
Section: Discussionsupporting
confidence: 77%
“…Furthermore, women with a prior history of breast cancer or a family history of breast cancer are eligible for a screening mammogram at any radiology practice, with the cost covered through Australia's public health system (Medicare). While population data on the number of women attending private screening facilities in Australia is unknown, in Queensland a recent population‐based study of 3,200 women diagnosed with breast cancer found that for approximately 20% of screen detected breast cancers, the screening mammogram was performed in the private system . Thus, overall participation in breast screening is likely to be higher than the numbers recorded by BreastScreen Australia.…”
Section: Introductionmentioning
confidence: 99%
“…Research efforts are needed to improve timely presentation in the latter group. Further, public health education campaigns about alarm symptoms remain important for improving awareness among minority groups and in the context of low- and middle-income countries [44] , [102] , [103] , [104] . For cancers with a broad symptom signature, promoting timely help-seeking is more challenging.…”
Section: Implications For Early Diagnosis Initiativesmentioning
confidence: 99%